Inovasi Daerah dalam Reformasi Pemerintahan Kota Tangerang Selatan dan Kota Magelang - Adi Suhendra (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2018)
This research is about governmental reform done by city government by using innovation. This research is motivated by the existence of local government of South Tangerang City and Magelang City in improving public service, governance and regulation. The purpose of this study is to explain the innovation of governance and public services at the city level. This research uses qualitative approach. Researchers use triangulation of data sources as a way to check the validity of data. Techniques of data retrieval, conducted by participant obervation, written documents, archives, official records, personal notes or notes and drawings to produce different evidence or data. While data processing researcher do data reduction. The results obtained in this study is the City of South Tangerang improve public services to facilitate the notary official of the land in the process behind the name. In addition, governance also becomes porgam priority in South Tangerang City is free treatment. As in the city of Magelang government reform is done innovation in the transportation service. This innovation brings online KIR checks with the intention of providing effective and efficient public services. The city of Magelang reforms governance by providing data in an integrated manner. Data in any regional device organization can be accessed via DataGo. An application to collect data and information in the government of Magelang City.